Study of Distribution Coefficient of 90Sr on Citumbuk Bentonite and Sukaramai Kaolinite - Budi Setiawan; Heni Suseno (EKSPLORIUM, 2017)
ABSTRACTThe study of distribution coefficient of strontium on bentonite and kaolinite samples, collected from Citumbuk, Bogor and Sukaramai, Padang, has been investigated under batch experiments. The sorption ratio was determined as a function of time, ionic strength and Sr concentration in the solution. The strontium wasextensively absorbed in the samples, with Kd values of 13,700 and 1,600 mL/g for bentonite and kaolinite samples respectively. The other results showed that ionic strength of the solution and initial concentration of Sr have given an effect to 90Sr sorption onto samples.ABSTRAKStudi tentang koefisien distribusi dari stronsium pada sampel bentonit dan kaolin yang diambil dari lokasi Citumbuk, Bogor dan Sukaramai, Padang, telah diteliti secara catu. Rasio penyerapan ditentukan sebagai fungsi waktu, kekuatan ionic dan konsentrasi Sr di larutan. Stronsium telah terserap dengan baik pada sampel, dengan nilai Kd adalah 13.700 dan 1.600 mL/g masing-masing untuk sampel bentonite dan kaolin. Hasil lainnya menunjukkan bahwa kekuatan ionik dan konsentrasi awal Sr di larutan telah memberikan pengaruh pada penyerapan 90Sr ke dalam sampel.